CONSIDERATIONS ON THE CONCEPT OF PERSONALIZING THE PENALTIES - ION RISTEA (Challenges of the Knowledge Society, 2013)
The adaptation of the constraint related to the committed offence is a mandatory request of equity, of principles deeply rooted in the individuals’ conscience namely that no sanction must overcome the gravity of the committed offence (suim cuique tribuiere – giving to each person what he deserves), principle that, in the concept of the Roman lawyers, was part of the fundamental principles of law (jus praecepta), along with other two principles: honestere vivere (having a honest life) and alterum non laedere (not harming another human being).